1983
DOI: 10.1177/073490418300100407
|View full text |Cite
|
Sign up to set email alerts
|

Failure Time of Loaded Wooden Beams During Fire

Abstract: A model is presented for predicting the failure time of loaded wooden beams of rectangular cross-section exposed to elevated temperatures or to fire. Failure times calculated by the model were compared to failure times measured in this study using 19.05 mm x 19.05 mm simply supported southern pine beams, and to failure times measured by the National Bureau of Standards during the fire of a full scale room. Reasonable agreements were found between the calculated failure times and the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The measured and calculated temperature and mass losses agreed well, supporting the validity of this first part of the model. The results given by the second and third parts of the model (changes in strengths and moduli and failure time) have only been compared to data obtained with wood [2,3]. Again, reasonable agreements were found between the data and the results of the model warranting extension of the model to organic matrix composites.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The measured and calculated temperature and mass losses agreed well, supporting the validity of this first part of the model. The results given by the second and third parts of the model (changes in strengths and moduli and failure time) have only been compared to data obtained with wood [2,3]. Again, reasonable agreements were found between the data and the results of the model warranting extension of the model to organic matrix composites.…”
Section: Discussionmentioning
confidence: 62%
“…In this paper such a model is outlined. The model has first been developed for predicting the changes in strengths and moduli of wood during fire [1][2][3]. Here the model is adapted to fiber reinforced organic matrix composites.…”
Section: Introduction He Mechanical Properties Of Fiber Reinforced Comentioning
confidence: 99%
“…Nonetheless, the data presented here indicate the usefulness of the model for estimating changes in the mechanical properties of wood exposed to elevated temperatures. Specifically, the model provides a suitable means for predicting failure times of wooden structures during fire exposure, a problem which is discussed in a companion article [3].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, knowledge of strength of load-bearing wooden structure elements exposed to elevated temperatures would be greatly helpful in designing wooden structures. The effect of temperature on the strength of wooden beams has been studied extensively [1][2][3][4][5][6][7]. It was found that, at as high a temperature as about 400°F, the strength of wood elements suffered only a slight reduction by less than 30%.…”
Section: Introductionmentioning
confidence: 99%